PEMANFAATAN KAYU BAKAU (Rhizopora sp.) SEBAGAI PONDASI RUKO DI KECAMATAN TEMBILAHAN DAN KORELASINYA TERHADAP KELESTARIAN HUTAN MANGROVE DI KABUPATEN INDRAGIRI HILIR - Novriandra, Aldryandes; Sribudiani, Evi; Sulaeman, Rudianda (Fakultas Kehutanan Universitas Lancang Kuning, 2015)
The purpose of this research was toknowed utilization mangrove tree (Rhizopora sp.) as foundation of shophouse and correlation to preservation mangrove forest in Indragiri Hilir Regency. Primary data is interview to know number of needs mangrove tree in unit area, source, and management mangrove wood in Tembilahan Subdistrict, Indragiri Hilir Regency. Secondary data is building lisence and extensive of mangrove forest in Indragiri Hilir Regency. Amount average requirement mangrove wood in an unit is 1500 stem with wood’s diameter 5 inch (10,2 cm) and length 7 m. Analysis use pearson correlation between requiment of mangrove wood as shophouse foundation in Tembilahan subdistrict and exetensive of mangrove forest and get ccorrelation coefficient was -0.54. it categories in medium class and don’t same direction. Based signification test show value 0,477 and mean is both variable is not significant.